Drawing : step-by-step - Box, Richard (Singapore : Page One, 2009)
A comprehensive guide, featuring a wide variety of drawing media including graphite, coloured pencils, charcoal, chalks, pastels conte crayons, water soluble pencils and pens, and techniques from making marks and creating tone and texture to mixing and overlaying colours
Includes index
Keywords: Colored pencil drawing -- Technique; Drawing -- Technique; Pencil drawing -- Technique